Student Data Governance Based on Office Administration at TK DYAS Montessori School - Moh. Irwan Hadi (PALAPA, 2024)
Student data governance is an essential component of school administration; however, studies specifically examining student data governance in kindergarten institutions from an office administration perspective remain limited. This study aims to describe and analyze student data governance based on office administration at TK DYAS Montessori School. This study employed a descriptive qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving the kindergarten principal, administrative staff, classroom teachers, and parents as supporting informants. Data were analyzed through data condensation, data display, and conclusion drawing and verification, while trustworthiness was strengthened through source, technique, and time triangulation. The findings show that student data management includes data collection, recording, storage, updating, security, and utilization for administrative services, school reporting, communication with parents, and fulfillment of institutional documents. The main obstacles include incomplete documents, non-periodic data updating, archive classification that is not yet fully systematic, suboptimal integration of manual and digital archives, and the absence of detailed standard operating procedures. The school has responded to these obstacles through document completion, archive organization, simple digital recapitulation, internal coordination, and the formulation of administrative procedures. This study concludes that office administration plays a strategic role in improving the accuracy, accessibility, security, and accountability of student data in early childhood education institutions. Theoretically, this study contributes to the literature on school administration and student data governance in kindergarten contexts. Practically, it provides implications for strengthening administrative procedures, archive management, and data-based school services in early childhood education institutions.